The Philosophy of Obedience in War: A Clausewitzian Analysis - Adwin Wibisono (Parahyangan Catholic University, 2025)
This study examines the moral limits of obedience in military ethics through a reinterpretation of Clausewitz’s On War, particularly regarding the relationship between a soldier’s compliance, the teleological purpose of war, and the moral agency of individuals within the chain of command. The research responds to concerns about the persistent strength of absolutist obedience doctrines in modern military institutions, which—across numerous historical cases such as My Lai and Abu Ghraib—have contributed to atrocities and the delegitimization of war. Using a qualitative method based on literature study and conceptual-critical analysis, this article analyzes Clausewitz’s texts, the doctrine of Auftragstaktik, historical investigation reports, and contemporary literature on military ethics, just war theory, and strategic leadership. The findings demonstrate three key points. First, Clausewitz views war as a political instrument directed toward teleological ends such as the restoration of order and the achievement of peace; therefore, obedience holds moral value only insofar as it supports these highest strategic purposes. Second, the analysis of the My Lai massacre and the abuses at Abu Ghraib confirms that blind obedience produces moral and strategic failure when orders are executed without rational judgment or ethical reflection. Third, integrating Clausewitz’s ideas with the principles of Auftragstaktik generates two new normative concepts—critical obedience and ethical disobedience—which position soldiers as responsible moral agents rather than mere executors of commands. These concepts offer an ethical foundation for modern military professionalism, particularly within the context of multidomain warfare and the complex frictions of contemporary conflict. Theoretically, this research contributes original insight to the field of military ethics by proposing a teleological framework that fills gaps in just war studies, professional military ethics, and character education for soldiers. This approach opens new pathways for developing military ethics curricula, reforming command doctrines, and establishing protective mechanisms for soldiers when confronted with erroneous or immoral orders.